A bio-relevant supramolecular Co(ii)-complex for selective fluorescence sensing of μM range inorganic As(iii) in aqueous medium and its intracellular tracking in bacterial systems. Issue 13 (12th March 2019) - Dhibar, Subhendu; Yadav, Priya; Paul, Tanima; Sarkar, Keka; Chattopadhyay, Asoke Prasun; Krawczuk, Anna; Dey, Biswajit
Abstract : A bio-relevant fluorescent supramolecular Co(ii )-complex selectively detects μM range toxic inorganic As(iii ) in water and in bacterial systems. Abstract : A novel Co(ii )-complex i.e. [Co( n -BuM)(DPA)(H2 O)2 ]·H2 O [ n -BuMH2 = n -butylmalonic acid and DPA = 2, 2′-dipyridylamine] was synthesized. The supramolecular feature, i.e. a metal coordinated and free guest water mediated hydrogen-bonding interaction assisted supramolecular π⋯π assembly, has been observed in the crystal structure of the Co(ii )-complex in the solid state. The role of different water molecules (metal coordinated and free guest water molecules) had also been scrutinized via theoretical studies. The fluorescent nature of the aqueous solution of the Co(ii )-complex has been utilized for selective μM range toxic inorganic As(iii )-sensing in aqueous medium. The Co(ii )-probe is very specific towards toxic As(OH)3 even in the presence of several ions and other arsenic sources like inorganic As(v )-oxoanions and organic arsenic species like cacodylic acid. The bio-relevant nature of the fluorescent probe of the Co(ii )-complex has also been examined. The luminous Co(ii )-probe has been employed for the intracellular tracking of As(iii ) in bacterial systems including As(iii )-resistant bacteria Bacillus aryabhattai and As(iii ) non-resistant bacteria Bacillus subtilis .